ANALISIS PORTOFOLIO SAHAM SYARIAH PADA JAKARTA ISLAMIC INDEKS PADA BURSA EFEK JAKARTA - Poerwanto .; Heru Sylvanata (Journal of Management and Business, 2005)
Commonstock portfolio analysis was important contributing to determine a good investment in the capital market. There was a way to know the optimal expected risk and return of the stock.    The purpose of this research for knowing level of commonstock Beta that listed in Jakarta Islamic Index and for guidance diversification process and find the optimal portfolio for the member of this combination.Based on analysis of commonstock historical data, we obtain 5 stocks with highest beta and above security market line, therefore this stocks place as portfolio member. We combine these five stocks with combination equation and resulting in 26 combinations. By using indifferent curve tools, we obtain 4 efficient portfolios.The result of this study were 4 optimal portfolio, which are: (1) Combination of 2 stocks, UNTR and BRPT, that give 12,72222 return and 19,999994 risk, (2) Combination of  3 stocks, UNTR, BRPT, PTBA, that give 9,3586% return and 12,4609% risk, (3) Combination of 3 stocks SMGR, UNTR, and BRPT that give 3,930% return and 6,325% risk, (4) Combination of 3 stocks, SMGR, AALI, and UNTR, that give 3,930 % return and 6,325% risk.This research can be used as reference for investor or potential investor in syariah stock exchange regarding of less information about stocks in the market today.